INTERPRETASI DEMOKRASI DALAM SISTEM MEKANIS TERBUKA PEMILIHAN UMUM DI INDONESIA - Antari, Putu Eva Ditayani (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2018)
General election is an important means for the state to ensure the implementation of a government that obtains the legitimacy of the people. In addition, the general election also aims to uphold democracy within sovereign states and ensure the implementation of the human rights of the citizens. Likewise in Indonesia, which periodically conducts general elections every 5 (five) years. General elections in Indonesia have undergone a shift from closed mechanical systems to open mechanical systems since 2004. This is influenced by the reforms that uphold the democracy and sovereignity, as well as respect for the political rights of citizens. The open mechanical system has variations since its use in 2004 to date, especially concerning the valid vote in the election. Therefore, this research will focus on analysing democracy that is being implemented in the election through open mechanical system, and various variations in open mechanical mechanical system in Indonesia. This research will be conducted by using normative research method by using primary legal materials in the form of laws governing the election, as well as secondary legal materials from various literature and scientific articles related to the problems discussed in the research. The results will be presented iin the form of problem description with analysis of the variety of open mechanical systems practiced in Indonesia. This study portrays the elections that are carried out honestly has manifested democracy and sovereignty of the people in the country. Furthermore there are various weaknesses of democratic interpretation in the variation of the implementation of open mechanical systems in elections in Indonesia.